Clinical and morphological estimation of radiation therapy efficiency in adults with medulloblastoma - Semenova, Vera; Lisianyi, Oleksandr (Ukrainian Neurosurgical Journal, 2015)
Introduction. Concerning the relevance of estimation of radiation therapy (RT) efficiency in adults with cerebellar medulloblastoma, histological features of therapeutic pathomorphosis in tumors tissue after RT studied. Materials and methods. Comparative aspects of medulloblastomas histological structure investigated in 24 adult patients before and after RT using biopsy material at first and repeated operations. Results. Based on assessment of cell-tissue changes severity in medulloblastoma in adults after RT we installed individual differences of sensitivity to RT in most of them. Conclusions. Standard RT course in adults with medulloblastoma after surgery induces in tissue of most “treated” tumors cytotoxic and cytodestructive effect that correlates with disease-free period prolongation.